Staphylococcal nuclease removes Escherichia coli and Klebsiella pneumoniae previously adhered to uroepithelial cells - T. Ibraheem, Hind; F. Al-Mathkhury, Harith J. (Iraqi Journal of Science, 2023)
Twenty-seven S. aureus isolates were obtained from patients referring various hospitals in Baghdad. Only 17 isolates produced DNase. SNase was extracted and purified from Saphylococcus aureus 3 isolate since it produces the largest zone of clearance on DNase agar. Nevertheless, only those phenotypically-producer of DNase harboured nuc gene. Present study revealed that the crude enzyme had a specific activity of 50.66 unit/mg; while it reached 241 unit/mg after ion exchange chromatography using carboxymethyl cellulose column. SDS-PAGE showed a single sharp band with an approximately 16.8 kDa molecular weight. A matter indicates that the enzyme is consistently pure. Results proved that SNase was able to significantly (P< 0.05) reduce the number of the uropathogens; Escherichia coli and Klebsiella pneumoniae attached to the uroepithelial cells.